Anomalous diffusion of mRNA in the cytoplasm of HeLa cells - Roessler, Ryan, author; Krapf, Diego, advisor; Stasevich, Tim, committee member; Prasad, Ashok, committee member (Colorado State University. Libraries, 2024)
Information about the diffusive motion of RNA would provide insights into intracellular structures and functions, as well as gene expression and genetic regulation. We study the motion of individual messenger RNA molecules in the cytoplasm of HeLa cells. RNAs are imaged in live cells via total internal reflection (TIRF) microscopy. In order to visualize individual RNA molecules expressing the MYH9 gene, they were labeled via MS2 stem loops bound to coat proteins tagged with the HaloTag-JF646 fluorophore. We then used single-particle tracking to obtain trajectories of individual molecules. Trajectories were analyzed in terms of their mean-squared displacement (MSD) and power spectral density (PSD). We observed non-ergodic, subdiffusive behavior, with statistics that depend on observation time, i.e., aging. Additionally, we observe stochastic switching between two mobility states with an order of magnitude difference in diffusivity. This switching process is responsible for the aging nature of the system. When compared to the cytoplasmic motion of synthetic nanoparticles, the analysis of RNA trajectories gives rise to discrepancies that raise questions about specific intracellular interactions.